Laboratory Culture and Life Cycle of Thelazia callipaeda in Intermediate and Definitive Hosts - Lingjun Wang; Di Li; Changzhu Yin; Hongri Tang; Bo Luo; Rong Yan; Yujuan Shen; Hui Liu (Pathogens, 2022)
Human thelaziasis caused by Thelazia callipaeda is being increasingly reported worldwide. Notably, an epidemic trend is observed in Southwest China. Whether Phortica okadai found in Southwest China can act as a vector of T. callipaeda and human-derived T. callipaeda animal infections has not been widely reported. Here, P. okadai was maintained in a laboratory and experimentally infected with first-stage larvae collected from adult T. callipaeda that were isolated from infected human subjects. Dead P. okadai were subjected to PCR assay and dissected every two days to detect T. callipaeda. Subsequently, live flies were used to infect a rabbit. The infection procedures were performed once a day (20 min) for two weeks. The results show that L1 collected from the adult T. callipaeda could successfully parasitize P. okadai captured in Zunyi, a city in Southwest China, and developed into L3, and a rabbit was successfully infected with T. callipaeda using P. okadai as the intermediate host. The present study demonstrates a human-derived T. callipaeda infection in rabbits, through P. okadai, under laboratory conditions for the first time. These results provide insights into the transmission cycle of T. callipaeda and constitute a foundation to develop an effective treatment protocol for T. callipaeda infection.